2021
DOI: 10.7717/peerj.10589
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in severe traumatic brain injury patients and its association with thirty-day mortality: a prospective observational cohort study in Uganda

Abstract: Background Traumatic brain injury (TBI) is a growing public health concern that can be complicated with an acute stress response. This response may be assessed by monitoring blood glucose levels but this is not routine in remote settings. There is a paucity of data on the prevalence of hyperglycemia and variables associated with mortality after severe TBI in Uganda. Objective We aimed to determine the prevalence of hyperglycemia in patients with severe TBI and variables associated with 30-day mortality at Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Unlike other brain pathologies, such as ischemic stroke and intracerebral hemorrhage, the target blood glucose range for TBI has not been well documented. Although 6.0–10.0 mmol/L was predicted as the appropriate target range of blood glucose [ 1 , 22 ], this range has not been fully substantiated by clinical research. In a previous stud y[ 15 ], based on the effect of IIT on 3- and 6-month survival and GOS, we found that the medium-control IIT group exhibited the best GOS compared to the tight-control IIT group and slight-control IIT group, while mean glucose levels in the medium-control group fell in the range of 7.1 to 13.0 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other brain pathologies, such as ischemic stroke and intracerebral hemorrhage, the target blood glucose range for TBI has not been well documented. Although 6.0–10.0 mmol/L was predicted as the appropriate target range of blood glucose [ 1 , 22 ], this range has not been fully substantiated by clinical research. In a previous stud y[ 15 ], based on the effect of IIT on 3- and 6-month survival and GOS, we found that the medium-control IIT group exhibited the best GOS compared to the tight-control IIT group and slight-control IIT group, while mean glucose levels in the medium-control group fell in the range of 7.1 to 13.0 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) leads to death and disability in patients. Secondary brain injury significantly affects the prognosis of patients with TBI, while hyperglycemia is one of the important factors inducing secondary brain injury [ 1 ]. Recent studies have confirmed that hyperglycemia aggravates nerve damage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary injury is a complex process that occurs in the hours and days after primary injury, which encompasses cranial and systemic complications. Matovu et al [ 72 ] showed that 1 in 6 patients with severe TBI admitted to a hospital in Uganda had blood glucose levels higher than 11.1 mmol/L. Patients with hyperglycemia were 1.47 times more likely to die within 30 days compared to those with no hyperglycemia, but this association was not statistically significant (OR: 1.47; 95% CI [0.236–9.153], p = 0.680).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other brain diseases, such as ischemic stroke and intracerebral hemorrhage, the target blood glucose range for TBI has not been well documented. Although 6.0-10.0 mmol/L was predicted as the appropriate target range of blood glucose [1,22], this range was not fully substantiated by clinical research. In a previous study, based on the effect of IIT on 3and 6-month survival and GOS, we introduced that the blood glucose between 7.1 and 13.0 mmol/L would be the suitable target range for controlling hyperglycemia with insulin therapy following TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) leads to death and disability in patients with trauma. Secondary brain injury affects the prognosis of patients with TBI signi cantly, while hyperglycemia is one of the important factors inducing secondary brain injury [1]. Recent studies con rmed that hyperglycemia could aggravate the damage of nerve function [2].…”
Section: Introductionmentioning
confidence: 99%